Prevalence of tobacco smoking and associated factors among adults in Ethiopia: a systematic review and meta-analysis - Daba, Chala; Atamo, Amanuel; Debela, Sisay Abebe; Dagne, Mengesha; Desye, Belay; Gebrehiwot, Mesfin (Frontiers in Public Health, 2024)
The public health concern of tobacco smoking is more prevalent in low-and middle-income countries including Ethiopia. Various studies have investigated tobacco smoking in various parts of Ethiopia. However, the findings have been inconsistent and characterized by significant variability. Besides, there is no nationally representative data on the subject, which could deter the design of effective intervention strategies to reduce tobacco-related problems.Therefore, this study aimed to estimate the pooled prevalence of tobacco smoking and associated factors among adults in Ethiopia.The study was conducted based on the Preferred Reporting Items for Systematic Reviews and Meta-Analysis Protocols Guideline. A detailed search was conducted from international databases including PubMed, Cochrane Library, Science Direct, CINAHL, African Journals Online, HINARI, Global Health, and Google Scholar. The extracted data was analyzed using STATA 14 software. A random-effects model was used to estimate the effect size. The Egger regression test and I 2 statistics were used to determine potential publication bias and heterogeneity among the reviewed articles, respectively.Results: A total of 32 studies with 69,897 study participants were included in this systematic review and meta-analysis. The pooled prevalence of lifetime tobacco smoking among adults in Ethiopia was 16.0% (95% confidence Interval (CI): 13.6-18.39) and there was significant heterogeneity among the included studies (I 2 = 99.1%, p < 0.001). Male adults were three times more likely to smoke tobacco as compared with females [OR= 3.22 (95% CI: 2.06-5.03)]. Being an alcohol user ] and tobacco-smoking friends ] are potential determinant factors for tobacco smoking.The pooled prevalence of lifetime and current tobacco smoking among adults in Ethiopia was high, which calls for urgent intervention. Therefore, prioritization of tobacco control strategies, such as creating awareness about the public health importance of tobacco smoking, can help prevent and mitigate the effects of tobacco smoking. Alcohol control law enforcement should also be strengthened.